Respostas

  • Usuário do Brainly
2014-06-29T13:20:18-03:00
 x^{4} -3 x^{2} =4

 x^{4} -3 x^{2} -4=0

 x^{2} =y

 y^{2} -3y-4=0

Δ=9+16
Δ=25

y'= \frac{3+5}{2} = \frac{8}{2} =4

y"= \frac{3-5}{2} = \frac{-2}{2} =-1


como x²=y
x²=4
x=+ou-√4
x'=2
x"=-2

x²=-1
x=√-1 (não  existe)

S={-2, 2}

 y^{4} -5x^{2} -36=0

y²=x

x²-5x-36=0

Δ=25+144
Δ=169
√169=13

x'= \frac{5+13}{2} = \frac{18}{2} =9

y"= \frac{5-13}{2} = \frac{-8}{2} =-4

como  y²=x

y²=9
y=+ou-√9
y=+ou-3

y'=3

y"=-3

y²=-4
y=√-4  (não existe)

S={-3,3}
2 5 2
2014-06-29T14:14:04-03:00